The impact of sleep on the health of higher education students: Literature review - Mariano, Pedro Henrique Mendonça; Cordeiro, Amanda Almeida; de Oliveira, Mariana Fernandes Zanon; Cardoso, Carolina Teixeira; Roriz, Bruna Noronha; Bezerra, Pedro Paulo Damasceno; Tocantins, Leon Bamolie Condorcet; Faria, Raphaela da Silva; Samora, Giovana Franco; Moraes, Marcella Silva (Seven Editora, 2023)
Introduction: The study of sleep-in medicine is recent and assessing health impacts is a current necessity. Healthy sleep and sleep hygiene are fundamental for the proper functioning of the nervous system, with significant impacts on physical and mental health, including for higher education students, who have a change in their routine in the face of the new challenges experienced when entering this new stage of life. Objective:  to analyze and synthesize the most recent research on the impact of sleep on the health of higher education students, in order to identify the consequences and the most effective approaches. Methodology: The searches were performed in the PUBMED and LILACS databases, using the search process through vocabulary controlled through descriptors and Boolean operators "and" and "or". Conclusion: Sleep plays a fundamental role in physical and mental health. Deprivation or an unregulated sleep routine can cause several consequences in relation to the health of the university student, the most common are: Hypertension, Metabolic Syndrome, stress, depression and other mental disorders. These are impacts that often become irreversible and decrease life expectancy. Sleep hygiene measures are simple and very effective forms of treatment, but the change in lifestyle habits is complex adaptationsDOI:https://doi.org/10.56238/globalhealthprespesc-058